1 - Cabo Verde à beira da revolução”: a emergência do pan-africanismo cabo-verdiano e os protestos em África - Lima, Redy Wilson; Vicente, Stephanie Duarte (Africa Development, 2023)
The history of Cape Verde is a history of anti-colonial resistance and revolts. Therefore, it has not escaped the social protests that have arisen in all African cities since the 2000s, which had, on 30 March 2015 and on 5 July 2017, its largest street demonstrations and rap as its main speaker and political messenger. This article based on qualitative research conducted in the cities of Praia and Mindelo – the stage of these demonstrations – aims to analyse the following points: the socio-political context of the emergence of the protests in Cape Verde; their nature and connection with African protests and pan-African ideology; and the role played by rap in this process.